Survival of a fetus after advanced abdominal pregnancy-challenging obstetric concern: a case report - Alam, Saima; Shahena Akter (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Abdominal pregnancy is a very rare form of ectopic pregnancy with very high morbidity and mortality for both mother and fetus. A 29 years old Bangladeshi woman presented from a rural area to Chittagong medical college hospital for first gynecological evaluation after 36 weeks of amenorrhea and lower abdominal pain. An ultrasound revealed a live fetus with sub amniotic collection and possibility of ruptured uterus. Laparotomy was done and a live fetus weighing 2500 gm was delivered. Placenta was adhered with both GIT and bladder. Placenta kept in situ and injection MTX given postoperatively. After re-laparotomy for postoperative pelvic abscess and hemoperitoneum, placental tissue removed and hemostasis maintained. Both mother and fetus are discharged in good health. A live fetus can be delivered after an advanced abdominal pregnancy. Whether the placenta should be kept in situ or removed, it is controversial. After medical literature review, we propose a management in this regard. Advanced abdominal pregnancy is extremely rare diagnosis and requires a high index of suspicion. The life-threatening complication is bleeding from the detached placental site. Placenta should be kept in situ to avoid intraoperative bleeding. Placenta involution during follow-up can be revealed by ultrasound, color Doppler and β-HCG serum level decrease.